Quasi in-situ analysis of fracture path during cyclic loading of double-edged U notched additively manufactured FeCo alloy - Pramanik, Sudipta; Andreiev, Anatolii; Hoyer, Kay-Peter; Schaper, Mirko (International Journal of Fatigue)
Keywords: Industrial and Manufacturing Engineering; Mechanical Engineering; Mechanics of Materials; General Materials Science; Modeling and Simulation

Bioresorbable AgCe and AgCeLa alloys for adapted Fe-based implants - Krüger, Jan Tobias; Hoyer, Kay-Peter; Schaper, Mirko (Materials Letters)
Keywords: Mechanical Engineering; Mechanics of Materials; Condensed Matter Physics; General Materials Science

Correlation between Taylor Model Prediction and Transmission Electron Microscopy-Based Microstructural Investigations of Quasi-In Situ Tensile Deformation of Additively Manufactured FeCo Alloy - Pramanik, Sudipta; Tasche, Lennart; Hoyer, Kay-Peter; Schaper, Mirko (Journal of Materials Engineering and Performance)
Abstract Within this research, the multiscale microstructural evolution before and after the tensile test of a FeCo alloy is addressed. X-ray µ -computer tomography (CT), electron backscattered diffraction (EBSD), and transmission electron microscopy (TEM) are employed to determine the microstructure on different length scales. Microstructural evolution is studied by performing EBSD of the same area before and after the tensile test. As a result, $$\langle$$ ⟨ 001 $$\rangle$$ ⟩ ||TD, $$\langle$$ ⟨ 011 $$\rangle$$ ⟩ ||TD are hard orientations and $$\langle$$ ⟨ 111 $$\rangle$$ ⟩ ||TD is soft orientations for deformation accommodation. It is not possible to predict the deformation of a single grain with the Taylor model. However, the Taylor model accurately predicts the orientation of all grains after deformation. {123} $$\langle$$ ⟨ 111 $$\rangle$$ ⟩ is the most active slip system, and {112} $$\langle$$ ⟨ 111 $$\rangle$$ ⟩ is the least active slip system. Both EBSD micrographs show grain subdivision after tensile testing. TEM images show the formation of dislocation cells. Correlative HRTEM images show unresolved lattice fringes at dislocation cell boundaries, whereas resolved lattice fringes are observed at dislocation cell interior. Since Schmid’s law is unable to predict the deformation behavior of grains, the boundary slip transmission accurately predicts the grain deformation behavior.
Keywords: Mechanical Engineering; Mechanics of Materials; General Materials Science

Novel AgCa and AgCaLa alloys for Fe-based bioresorbable implants with adapted degradation - Krüger, Jan Tobias; Hoyer, Kay-Peter; Filor, Viviane; Pramanik, Sudipta; Kietzmann, Manfred; Meißner, Jessica; Schaper, Mirko (Journal of Alloys and Compounds)
Keywords: Materials Chemistry; Metals and Alloys; Mechanical Engineering; Mechanics of Materials

Anisotropic Ion Migration and Electronic Conduction in van der Waals Ferroelectric CuInP2S6 - Zhang, Dawei; Luo, Zheng-Dong; Yao, Yin; Schoenherr, Peggy; Sha, Chuhan; Pan, Ying; Sharma, Pankaj; Alexe, Marin; Seidel, Jan (Nano Letters)
Keywords: Mechanical Engineering; Condensed Matter Physics; General Materials Science; General Chemistry; Bioengineering

A Method for Characterization of Geometric Deviations in Clinch Points with Computed Tomography and Transient Dynamic Analysis - Köhler, Daniel; Sadeghian, Behdad; Kupfer, Robert; Troschitz, Juliane; Gude, Maik; Brosius, Alexander (Key Engineering Materials)
When joining lightweight parts of various materials, clinching is a cost efficient solution. In a production line, the quality of a clinch point is primarily controlled by measurement of dimensions, which are accessible from outside. However, methods such as visual testing and measuring the bottom thickness as well as the outer diameter are not able to deliver any information about the most significant geometrical characteristic of the clinch point, neck thickness and undercut. Furthermore, ex-situ destructive methods such as microsectioning cannot detect elastic deformations and cracks that close after unloading. In order to exceed the current limits, a new non-destructive in-situ testing method for the clinching process is necessary. This work proposes a concept to characterize clinch points in-situ by combining two complementary non-destructive methods, namely, computed tomography (CT) and ultrasonic testing. Firstly, clinch points with different geometrical characteristics are analysed experimentally using ex-situ CT to get a highly spatially resolved 3D-image of the object. In this context, highly X-ray attenuating materials enhancing the visibility of the sheet-sheet interface are investigated. Secondly, the test specimens are modelled using finite element method (FEM) and a transient dynamic analysis (TDA) is conducted to study the effect of the geometrical differences on the deformation energy and to qualify the TDA as a fast in-situ non-destructive method for characterizing clinch points at high temporal resolution.
Keywords: Mechanical Engineering; Mechanics of Materials; General Materials Science

Computed tomography investigation of the material structure in clinch joints in aluminium fibre-reinforced thermoplastic sheets - Gröger, Benjamin; Köhler, Daniel; Vorderbrüggen, Julian; Troschitz, Juliane; Kupfer, Robert; Meschut, Gerson; Gude, Maik (Production Engineering)
Abstract Recent developments in automotive and aircraft industry towards a multi-material design pose challenges for modern joining technologies due to different mechanical properties and material compositions of various materials such as composites and metals. Therefore, mechanical joining technologies like clinching are in the focus of current research activities. For multi-material joints of metals and thermoplastic composites thermally assisted clinching processes with advanced tool concepts are well developed. The material-specific properties of fibre-reinforced thermoplastics have a significant influence on the joining process and the resulting material structure in the joining zone. For this reason, it is important to investigate these influences in detail and to understand the phenomena occurring during the joining process. Additionally, this provides the basis for a validation of a numerical simulation of such joining processes. In this paper, the material structure in a joint resulting from a thermally assisted clinching process is investigated. The joining partners are an aluminium sheet and a thermoplastic composite (organo sheet). Using computed tomography enables a three-dimensional investigation that allows a detailed analysis of the phenomena in different joining stages and in the material structure of the finished joint. Consequently, this study provides a more detailed understanding of the material behavior of thermoplastic composites during thermally assisted clinching.
Keywords: Industrial and Manufacturing Engineering; Mechanical Engineering

Characterisation of lateral offsets in clinch points with computed tomography and transient dynamic analysis - Köhler, D.; Sadeghian, B.; Troschitz, J.; Kupfer, R.; Gude, M.; Brosius, A. (Journal of Advanced Joining Processes)
Keywords: Mechanical Engineering; Mechanics of Materials; Engineering (miscellaneous); Chemical Engineering (miscellaneous)

Strength enhancement of AlMg sheet metal parts by rapid heating and subsequent cold die stamping of severely cold-rolled blanks - Camberg, Alan Adam; Andreiev, Anatolii; Pramanik, Sudipta; Hoyer, Kay-Peter; Tröster, Thomas; Schaper, Mirko (Materials Science and Engineering: A)
Keywords: Mechanical Engineering; Mechanics of Materials; Condensed Matter Physics; General Materials Science

Spin Polarization, Electron–Phonon Coupling, and Zero-Phonon Line of the NV Center in 3C-SiC - Jurgen von Bardeleben, Hans; Cantin, Jean-Louis; Gerstmann, Uwe; Schmidt, Wolf Gero; Biktagirov, Timur (Nano Letters)
Keywords: Mechanical Engineering; Condensed Matter Physics; General Materials Science; General Chemistry; Bioengineering

The effect of triphenyl phosphate inhibition on flame propagation over cast PMMA slabs - Trubachev, S.A.; Korobeinichev, O.P.; Karpov, A.I.; Shaklein, A.A.; Glaznev, R.K.; Gonchikzhapov, M.B.; Paletsky, A.A.; Tereshchenko, A.G.; Shmakov, A.G.; Bespalova, A.S.; Yuan, Hu; Xin, Wang; et al. (Proceedings of the Combustion Institute)
Keywords: Physical and Theoretical Chemistry; Mechanical Engineering; General Chemical Engineering

Encrypted polynomial control based on tailored two‐party computation - Schulze Darup, Moritz (International Journal of Robust and Nonlinear Control)
Keywords: Electrical and Electronic Engineering; Industrial and Manufacturing Engineering; Mechanical Engineering; Aerospace Engineering; Biomedical Engineering; General Chemical Engineering; Control and Systems Engineering

Optimal event‐triggered transmission scheduling for privacy‐preserving wireless state estimation - Lu, Jingyi; Leong, Alex S.; Quevedo, Daniel E. (International Journal of Robust and Nonlinear Control)
Keywords: Electrical and Electronic Engineering; Industrial and Manufacturing Engineering; Mechanical Engineering; Aerospace Engineering; Biomedical Engineering; General Chemical Engineering; Control and Systems Engineering

Refill friction stir spot and resistance spot welding of aluminium joints with large total sheet thicknesses (III-1965-19) - Schmal, Christopher; Meschut, Gerson (Welding in the World)
Refill friction stir spot welding (RFSSW) is a highly flexible and promising solid-state joining method for aluminium alloys. Alternatively, resistance spot welding (RSW) can be stated as an appropriate joining method which can be automated and used within a high-volume production due to short process times. Both processes do not need any additional elements and a flat surface on both sides of the joints can be realised. In order to meet the modern requirements for crash safety and structural stiffness, thermal and mechanical joining methods are mainly combined by using single-component epoxy resin adhesives. Due to an insufficient knowledge about the application of both thermal joining methods for the abovementioned material combinations combined with additional adhesives, deeper investigations were done regarding the interactions of the polymers and the joining processes. Starting with a brief presentation of the boundary conditions of the investigations and the refill friction stir spot welding and resistance spot welding of high-strength aluminium alloys with sheet thicknesses bigger than 5.8 mm, the paper introduces the process-related joint properties of friction-based and resistance-based welded joints. Afterwards, the paper discusses the influences of the process parameter on the metallographic joint formation and load-bearing capacities for a selected two-sheet and four-sheet material combination. When combining the spot welding technologies with adhesives, the process parameters of the RFSSW process have to be adapted for the two-sheet combination by adding a squeeze-out step, while for RSW, just the preholding time has to be increased. Different challenges for both joining methods are shown. For RFSSW, the gap formation has to be considered when welding big total sheet thicknesses, while for RSW, the shape of the weld nugget is more important for an appropriate joint performance. Additionally, process optimisations for less adhesive incineration will be discussed for both joining processes, and the influences of the adhesive on the joint formation will be addressed with the help of load-bearing capacity evaluations. The paper closes with specific recommendations for the realisation of refill friction stir and resistance spot-welded joints with and without adhesive in the field of Al joints with big total sheet thicknesses which meet the quality demands and an outlook for further research steps will be given.
Keywords: Metals and Alloys; Mechanical Engineering; Mechanics of Materials

Early stage crack detection in mechanically joined steel/aluminum joints by condition monitoring - Gollnick, Maik; Giese, Patrick; Hein, David; Meschut, Gerson; Herfert, Daniel (Materials Testing)
Monitoring systems for machines, plants, materials and equipment are increasingly used in production processes. These online condition monitoring systems can detect damage or excessive loads at an early stage and can drastically reduce or prevent long downtimes of plants and machines as well as high repair and maintenance costs. This paper depicts a method for online crack detection with pattern recognition methods for specimens joined by self-pierce riveting under cyclic load in fatigue tests (laboratory application). A software specially conceived for this application was developed. This software, AnrissMF, uses active acoustic testing with a structure-borne sensor to detect cracks in the joints at a very early stage. It is shown in this paper that this software can detect cracks much earlier than classical failure criteria for joints (i. e. before any drop in stiffness or frequency is observed). Furthermore, the successful application of software AnrissMF for online crack detection during the fatigue strength test is presented.
Keywords: Mechanical Engineering; Mechanics of Materials; General Materials Science

Process characteristics and influences of production-related disturbances in resistance element welding of hybrid materials with steel cover sheets and polymer core - Schmal, Christopher; Meschut, Gerson (Welding in the World)
Keywords: Metals and Alloys; Mechanical Engineering; Mechanics of Materials

Effect of substrate pre‐treatment on the low cycle fatigue performance of tungsten carbide‐cobalt coated additive manufactured 316 L substrates - Tillmann, Wolfgang; Hagen, Leif; Garthe, Kai-Uwe; Hoyer, Kay-Peter; Schaper, Mirko (Materialwissenschaft und Werkstofftechnik)
Keywords: Mechanical Engineering; Mechanics of Materials; Condensed Matter Physics; General Materials Science

Characterization of the fatigue behaviour for SAE 1045 steel without and with load-free sequences based on non-destructive, X-ray diffraction and transmission electron microscopic investigations - Wu, Haoran; Bill, T.; Teng, Z.J.; Pramanik, Sudipta; Hoyer, Kay-Peter; Schaper, Mirko; Starke, Peter (Materials Science and Engineering: A)
Keywords: Mechanical Engineering; Mechanics of Materials; Condensed Matter Physics; General Materials Science

Degradable silver‐based alloys - Andreiev, Anatolii; Hoyer, Kay-Peter; Grydin, Olexandr; Frolov, Yaroslav; Schaper, Mirko (Materialwissenschaft und Werkstofftechnik)
Keywords: Mechanical Engineering; Mechanics of Materials; Condensed Matter Physics; General Materials Science

Clinching in in-situ CT—A numerical study on suitable tool materials - Köhler, Daniel; Kupfer, Robert; Gude, Maik (Journal of Advanced Joining Processes)
Keywords: Mechanical Engineering; Mechanics of Materials; Engineering (miscellaneous); Chemical Engineering (miscellaneous)